Educational Reception in Rotterdam and Barcelona: Policies, Practices and Gaps - Bruquetas-Callejo, María (Amsterdam University Press, 2014)
The reception of newcomer youngsters by schools constitutes a policy issue in Europe already for decades. This book deals with how practitioners in Rotterdam and Barcelona apply existing policies for the reception of immigrant students, the dilemmas they face and the strategies they design as a response. Using a combination of discursive, organizational, and ethnographic research techniques, the author studies to what extent practices conform to policies, and to what extent they diverge from them in basic principles. This book analyzes the influence of institutional frameworks on the practices of policy implementers by comparing Netherlands and Spain -specifically Barcelona and Rotterdam-, two cases which are very different in terms of their national policies of integration, their educational systems and their programs for educational reception. Much can be learned over the reception practices of secondary schools, but above all over how policy gaps work, and the common and specific features that they present across different countries. In short, this is an indispensable reading for scholars, policymakers and practitioners alike, which offers new insights about the policy-practice gap and the role of policy practitioners in it.